Dimorphism and hydrocarbon metabolism in Yarrowia lipolytica var. indica - Palande, A. S.; Kulkarni, S. V.; Leon-Ramirez, C.; Campos-Gongora, E.; Ruiz-Herrera, J.; Deshpande, Mukund V. (Archives of Microbiology, 2014)
Yarrowia lipolytica is able to metabolize high Mr hydrophobic natural compounds such as fatty acids and hydrocarbons. Characteristically, strains of Y. lipolytica can grow as populations with variable proportions of yeast and filamentous forms. In the present study, we describe the dimorphic characteristics of a variant designated as Y. lipolytica var. indica isolated from petroleum contaminated sea water and the effect of cell morphology on hydrocarbon metabolism. The variant behaved as a yeast monomorphic strain, under conditions at which terrestrial Y. lipolytica strain W29 and its derived strains, grow as almost uniform populations of mycelial cells. Using organic nitrogen sources and N-acetylglucosamine as carbon source, var. indica was able to form mycelial cells, the proportion of which increased when incubated under semi-anaerobic conditions. The cell surface characteristics of var. indica and W29 were found to be different with respect to contact angle and percent hydrophobicity. For instance, percent hydrophobicity of var. indica was 89.93 +/- A 1.95 while that of W29 was 70.78 +/- A 1.1. Furthermore, while all tested strains metabolize hydrocarbons, only var. indica was able to use it as a carbon source. Yeast cells of var. indica metabolized hexadecane with higher efficiency than the mycelial form, whereas the mycelial form of the terrestrial strain metabolized the hydrocarbon more efficiently, as occurred with the mycelial monomorphic mutant AC11, compared to the yeast monomorphic mutant AC1.
Keywords: Hexadecane metabolism; Yarrowia lipolytica; Yeast-mycelium transition